Youth suicidality and the role of maternal betrayal trauma, child maltreatment, and dissociative symptoms - Panisch, Lisa S. (Journal of family violence, 2023)
Betrayal trauma is associated with dissociative symptoms, which can increase the risk of suicidal thoughts and behaviors. Previous research demonstrates associations between a mother’s history of betrayal trauma and intergenerational patterns of maltreatment and dissociation among their children. However, maternal betrayal trauma history remains unexplored in the etiology of youth suicidality. This study was conducted to investigate pathways between maternal betrayal trauma and youth suicidality, while considering the influences of youth maltreatment exposure and symptoms of dissociation. We implemented conditional growth curve modeling in a structural equation modeling framework to analyze secondary data from the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN; N = 1,354; 51.48% female, 53.29% Black). Predictors included mothers’ betrayal trauma history, youth maltreatment exposure, and youth dissociative symptoms at ages 8, 12, and 16. The slope and intercept of dissociative symptoms at the age-8, age-12, and age-16 visit were modeled as latent factors. A robust weighted least squares estimator accounted for categorical outcomes. Indirect effects were assessed via the delta method. We found a significant indirect effect from maternal betrayal trauma to adolescent suicidal ideation through children’s maltreatment exposure and the growth in children’s dissociative symptoms from ages 8 through 16. Maternal betrayal trauma may play a unique role in perpetuating intergenerational patterns of trauma that contribute to subsequent trajectories of youth suicidality among their offspring. Practice implications for screening, prevention, and early intervention strategies are described, along with directions for further study.